A MONOGRAPH OF THE GENUS PARINARI Aubl. (Rosaceae-Chrysobalanoideae) IN ASIA AND THE PACIFIC REGION - A. J. G. H. KOSTERMANS (REINWARDTIA, 1965)
In the area 20 species (one cultivated) are recognized; furthermore one undescribed species is discussed.The genera Cyelaiulrophora Hassk. and Mara/tithes Bl. are segregated from Parinari proper. The genus is subdivided into 2 sections: Parinari and Anareolala.